2017
DOI: 10.1080/13543784.2017.1389896
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 blockade in breast cancer: current experience and future perspectives

Abstract: Dysregulated cellular proliferation, one of the hallmarks of cancer, is mediated by aberrant activation of the cell cycle machinery through the biological effects of cyclin-dependent kinases (CDKs). The clinical development of non-selective CDK inhibitors failed due to combined lack of efficacy and excessive toxicity reported by clinical trials across different cancer types. The clinical development of second generation, CDK4/6-selective inhibitors, namely palbociclib, abemaciclib and ribociclib, led to practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…41,42 While Roger PP's group supposed the phosphorylated CDK4 could potentially predict sensitivity to CDK4/6 blockade, 43 this was not confirmed later in clinical results. 44…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41,42 While Roger PP's group supposed the phosphorylated CDK4 could potentially predict sensitivity to CDK4/6 blockade, 43 this was not confirmed later in clinical results. 44…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical trial PALOMA‐1 identified that they had no association with PD 0332991 . While Roger PP's group supposed the phosphorylated CDK4 could potentially predict sensitivity to CDK4/6 blockade, this was not confirmed later in clinical results . Wang et al (2017) examined whether the expression of cyclin D3 and CDK6 is associated with palbociclib or ribociclib treatment through depletion of the antioxidants NADPH and glutathione .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that CDK4 and its functional homologue CDK6 play key roles in mammalian cell proliferation, where they help drive the progression of cells into the DNA synthesis (S) phase of the cell-division cycle. Additionally, the cyclin D1–CDK4/6 axis plays a central role in breast cancer development and maintenance [ 19 22 ]. Therefore, we conclude that the suppressive effects of CDK4 and CDK6 expression by miR-623 not only affect cancer cell proliferation, but also influence cancer cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib (PD-0332991; Ibrance®, Pfizer), is a reversible, selective CDK4/6 inhibitor. Palbociclib has been recently approved by the US FDA for treatment of patients with breast cancer [169]. In HCC cell lines, palbociclib promotes a reversible cell cycle arrest and the induction of cellular senescence, alone or in association with sorafenib [170] and enhances radiosensitivity [171].…”
Section: Agingmentioning
confidence: 99%